2018
DOI: 10.3892/ol.2018.8269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone on C6 cell proliferation, migration and invasion through the upregulation of AQP1

Abstract: Dexamethasone (Dex) is commonly used to treat glioma; however, the mechanism underlying the action of Dex remains unclear. In the present study, the hypothesis that aquaporin-1 (AQP1) may participate in tumor cell proliferation, apoptosis, migration and invasion was tested using small interfering RNA (siRNA). The results of the current study indicated that Dex could inhibit the proliferation, in addition to promoting the migration, of C6 cells. Dex was indicated to promote the expression of AQP1. Downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
3
14
2
Order By: Relevance
“…Glioma invasiveness has been linked to AQP1 overexpression [ 73 ], which is greater in migrating cells than in the tumor core [ 68 ]. Dexamethasone, which promotes AQP1 transcription, increases the invasiveness of glioma cells [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glioma invasiveness has been linked to AQP1 overexpression [ 73 ], which is greater in migrating cells than in the tumor core [ 68 ]. Dexamethasone, which promotes AQP1 transcription, increases the invasiveness of glioma cells [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Necrotic death of C6 cells can be induced by serum deprivation and DEX enhanced this cytotoxic effect through GR activation (Morita et al, 1999). In the same cell line, the anti-proliferative effect of DEX was shown to be dose and time dependent and to involve Aquaporin 1 (AQP 1 ; Guan et al, 2018). Indeed, DEX increased the mRNA and protein expression of AQP 1 .…”
Section: The Anti- and Pro-proliferative Effects Of Dexmentioning
confidence: 99%
“…Indeed, DEX increased the mRNA and protein expression of AQP 1 . Moreover, the effect of DEX on cell proliferation was abolished upon AQP 1 gene silencing (Guan et al, 2018). Surprisingly, by using U373 cells, Gündisch et al (2012) showed a pro-proliferative effect of DEX (Table 1).…”
Section: The Anti- and Pro-proliferative Effects Of Dexmentioning
confidence: 99%
“…During development and organogenesis, cell proliferation, migration, invasion, and cell-cell adhesion are frequently occurred. In these processes, AQP1, AQP3, and AQP4 have been suggested to be involved in such cellular processes [20][21][22][23][24]. Therefore, AQP5 may also play an important role in these developmental processes, although it is still unclear.…”
Section: Introductionmentioning
confidence: 99%